Contrasting plant ecological benefits endowed by naturally occurring EPSPS resistance mutations under glyphosate selection - Vila Aiub, Martín Miguel (2021)
Fil: Vila Aiub, Martín Miguel. University of Western Australia (UWA). School of Agriculture and Environment. Australian Herbicide Resistance Initiative (AHRI. Crawley, Western Australia, Australia.